Diseño de un sistema de gestión de la calidad bajo la norma ISO 9001:2008, en la empresa intramet - Ortiz Medina, Leydy Laura (2009)
This thesis must like objective design a System of Management of the Quality that works according to the requirements of Norm ISO 9001:2008, for Intramet (Industria de Transformación. Metalúrgica). The design of the System has been divided in 2 stages, first that correspond to the present situation analysis of the company where the present methods of work and processes are identified, allowing to know main real and potential the nonconformities, to secure between these a plan of continuous improvement for the company. In the second stage 9001:2008 is come with the development of the documentation according to the requirements of norm ISO and it is come to the elaboration of the quality manual, normative procedures and productive procedures, hoping that these facilitate a future implantation of the SGC designed in the company.